INGE'S THE TINY CLOSET IN GENDER PERSPECTIVE: RETAINING THE POLARISATION - G. M. Adhyanggono (Celt: A Journal of Culture, English Language Teaching & Literature, 2001)
This article is an overview toward a play of an American dramatist, William Inge. In this case, the play is viewed from gender perspective as considered 'quite representative' to reveal what Friedan (1995) stated as polarisation of men and women. The writer wants to depict the representation of men and women in the play as the central issue affecting the result of this analysis. In addition, the term gender should be understood as an umbrella term pervading the whole discussion. To what extent the verification of the polarisation may analytically come as the conclusion.